2012
DOI: 10.3748/wjg.v18.i24.3050
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of achalasia cardia

Abstract: Achalasia cardia is one of the common causes of motor dysphagia. Though the disease was first described more than 300 years ago, exact pathogenesis of this condition still remains enigmatic. Pathophysiologically, achalasia cardia is caused by loss of inhibitory ganglion in the myenteric plexus of the esophagus. In the initial stage, degeneration of inhibitory nerves in the esophagus results in unopposed action of excitatory neurotransmitters such as acetylcholine, resulting in high amplitude non-peristaltic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 76 publications
0
88
0
3
Order By: Relevance
“…1 Its pathogenesis is still enigmatic. [2][3][4] Genetic factors are likely to be important in its pathogenesis as supported by occasional familial aggregation, concordance among monozygotic twins and reports on association between achalasia and Hirshsprung's disease, a similar condition with genetic basis. [5][6][7] Esophageal aperistalsis and incomplete lower esophageal sphincter (LES) relaxation, the characteristic features of achalasia, result from degeneration of the ganglion cells in the myenteric plexus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Its pathogenesis is still enigmatic. [2][3][4] Genetic factors are likely to be important in its pathogenesis as supported by occasional familial aggregation, concordance among monozygotic twins and reports on association between achalasia and Hirshsprung's disease, a similar condition with genetic basis. [5][6][7] Esophageal aperistalsis and incomplete lower esophageal sphincter (LES) relaxation, the characteristic features of achalasia, result from degeneration of the ganglion cells in the myenteric plexus.…”
Section: Introductionmentioning
confidence: 99%
“…9 Nitric oxide (NO) is the most important inhibitory neurotransmitter of the esophageal myenteric plexus; it progressively delays muscular contraction in the distal esophagus preventing simultaneous contraction and relaxes LES during swallowing in healthy persons. 3 Degeneration of NO-containing neurons, therefore, causes simultaneous contraction in the esophageal body and failure of swallow-induced LES relaxation. 9,10 NO is synthesized by NO synthase (NOS), which has 3 isoforms, namely, endothelial NOS (eNOS), inducible NOS (iNOS), and neuronal NOS (nNOS).…”
Section: Introductionmentioning
confidence: 99%
“…An autoimmune etiology for AD has been consid¬ered because of the presence of neural inflammation in the absence of conclusive evidence of infection. Studies have demonstrated inflammatory cell infiltrate of the myen¬teric plexus in 90%-100% of esophageal specimens from AD patients [6]. Storch et al suggested a role of autoimmunity by demonstrating a higher prevalence of anti-myenteric autoantibody in AD (64%) [7].…”
Section: Discussionmentioning
confidence: 99%
“…in the serum of a subgroup of patients with achalasia (8)(9)(10)13). A cluster consisting of varied autoimmune diseases has been linked to achalasia: myasthenia gravis, polymyositis, autoimmune thyroid disease, among others, contributing to the argument that autoimmunity may be a cause for some idiopathic achalasia (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…However, some important findings are suggestive of an autoimmune mechanism: significant infiltration of the myoenteric plexus by monocytes, presence of the class II-Human Histocompatibility Complex DQwl antigen and antibodies to myoenteric neurons. Specifically, higher genotypic frequency of the human leukocyte antigen (HLA)-DQw1, DQA1*0101, DQA1*103, DQB1*0602, and DQB1*0603 alleles were observed in achalasia patients compared with controls (7,8,(10)(11)(12)(13). Descriptions of inflammatory infiltration in the affected regions of the esophagus in achalasia led to speculation of an autoimmune pathogenesis.…”
Section: Sumáriomentioning
confidence: 99%